Laboratory Testing of Polymer Flooding by Hydrolyzed Poly(acrylamide) in High Salinity Conditions - I. Gussenov; A. Shakhvorostov; A. Ayazbayeva; S.E. Kudaibergenov (Eurasian Chemico-Technological Journal)
This study investigates the efficacy of high molecular weight hydrolyzed polyacrylamide (HPAM) solutions in enhancing oil recovery under high salinity conditions. The viscosity values of 0.25 wt.% HPAM solutions in 250 g∙L─1 brine with high content of divalent cations (Ca and Mg) were found to range from 11.5 to 12.6 cP for both 10% and 30% hydrolysis polymers. The displacement of 420-cP oil from sand pack models showed that injecting 3 pore volumes (PVs) of polymer solutions significantly increased the oil recovery factor, with an increment of 16─28% after the injection of 1 PV of water. The results of fractional flow calculations, along with sand pack flooding experiments, suggest that the oil recovery factor measurements are most likely overestimated by roughly 10%. An explanation for this is the plugging of pores by high molecular weight polymers. In fact, as the molecular weight increased from low to medium high and super high, it required the assumption of a much higher viscosity to achieve a fit between fractional flow predictions and actual polymer flood results. These findings highlight the potential of high molecular weight HPAM solutions to enhance oil recovery in high salinity environments and underscore the importance of using both sand pack flooding experiments and fractional flow calculations for comparing different polymers.